High-level mosaicism for 45,X in 45,X/46, XY at amniocentesis in a pregnancy with a favorable fetal outcome and cytogenetic discrepancy in various tissues - Chih-Ping Chen; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Fang-Tzu Wu; Chen-Chi Lee; Chen-Wen Pan; Yun-Yi Chen; Wayseen Wang (Elsevier, 2022)
Objective: We present prenatal diagnosis of high-level mosaicism for 45,X by amniocentesis in a pregnancy with a favorable fetal outcome. Case report: A 35-year-old, gravida 2, para 1, woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype of 45,X[13]/46,XY[11]. Simultaneous array comparative genomic hybridization (aCGH) on uncultured amniocytes revealed the result of Yp11.3q11.21 × 0-1 [0.1], Yq11.21q11.23 × 0-1 [0.6]. At 19 weeks of gestation, she underwent the second amniocentesis which revealed a karyotype of 45,X[13]/46,XY[12], and aCGH and multiplex ligation-dependent probe amplification (MLPA) on uncultured amniocytes showed 37% mosaicism for Y-deleted cells. At 28 weeks of gestation, she underwent the third amniocentesis which revealed a karyotype of 45,X[25]/46,XY[25], and aCGH on uncultured amniocytes revealed the result of Yq11.21q11.23 × 0.5, Yq11.23q12 × 0.7. Interphase fluorescence in situ hybridization (FISH) analysis on uncultured amniocytes revealed that 16.67% (20/120 cells) were Y-deleted cells. The parental karyortypes and prenatal ultrasound were normal. At 37 weeks of gestation, a 2707-g phenotypically normal male baby was delivered with normal male external genitalia. The karyotypes of cord blood, umbilical cord and placenta were 45,X[25]/46,XY[15], 45,X[18]/46,XY[22] and 45,X[25]/46,XY[15], respectively. When follow-up at age five months, the neonate was normal in external genitalia and physical development. The peripheral blood had a karyotype of 45,X[29]/46,XY[11], and FISH analysis on 100 buccal mucosal cells showed no abnormal signals. When follow-up at age 11 months, the neonate was physically normal, and the peripheral blood had a karyotype of 45,X[17]/46,XY[23]. Conclusion: High-level mosaicism for 45,X in 45,X/46, XY at amniocentesis can be associated with a favorable fetal outcome despite the presence of cytogenetic discrepancy in various tissues.